Islamic and Jewish Law of Ḥalal & Ḥaram: AnalAysis of Similarities & Differences - Ikramullah, Muhammad; Junaid, Muhammad (Journal of Islamic and Religious Studies, 2017)
The world Semitic religions like Judaism, Christianity and Islam have given comprehensive regulations and code of life. Therefore; there has been a complete system and directions about “ḥalal” and “ḥaram” (kosher non-kosher) means legal and illegal (treif’ in Jewish law). As Islam gives clear cut directives in beliefs, worships, ethics, economy and ways of life to guide the men in life; similarly the Judaism has also given clear regulations in these fields to guide its followers. Islam has taught its followers to eat and drink ‘ḥalal’ (Tayyib), so Judaism has also stressed on eating only ‘kosher’ (food that can be consumed according to Jewish law). For example in animals; meat of cow, bull, sheep and goat etc are legitimizing for eating in both the religions. Similarly the meat of pig is not allowed for men. Many things are similar in both these religions regarding dietary law.This article describes about ‘ḥalal’ and ‘kosher’ things in detail and tells what the similarities and dissimilarities regarding dietary laws are found in their religious literatures.